Implementasi Makerspace di Perpustakaan Kota Yogyakarta - Rohmawati, Annisa (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
This article presents about a work produced by a society, which aims to train skills and add creativity. Makerspace is one person's or group's activities in producing a work. Works created new works or can be either recycle materials you have available. Works created new works or can be either recycle materials you have available. The city library is one of the libraries that have leveraged makerspace as regular activity in filling the holiday for children. There were taught how to make unique items made of unused materials and also made paintings that were created together. Enthusiasm of children is very high, they are very happy and enjoy the activities. To that end the need for activities in the library to add makerspace knowledge and hone skills for children. At the same time it is important to add to the attractiveness of the child to come to the library.